GREAT OF NECESSITIES OF COUNTRIES ECONOMICS IN THE RESOURCES OF BOWEL ON THE EARTH - Бодюк, А. (Київський національний університет імені Тараса Шевченка, 2010)
Analysis of publications is conducted from the problems of the use of bowels of the earth. Determination of concept vehicle of global necessities of economies of countries is given. The concepts of globalization of geological survey requirements are grounded. Researches of dynamics and pattern of requirements of economies of countries are actual for economic geology.

Проведено аналіз публікацій з проблем використання надр. Дано визначення понятійного апарату глобальних потреб економік країн у корисних копалинах. Обґрунтовано поняття глобалізації потреб у геологорозвідці в широкому і вузькому значеннях. Визначено дослідження які актуальні для економічної геології у світовому масштабі динаміки і структури потреб економік країн.
ГЛОБАЛЬНІ ПОТРЕБИ ЕКОНОМІК КРАЇН У РОЗВІДЦІ НАДРОВИХ РЕСУРСІВ